Cystatin C, creatinine, estimated glomerular filtration, and long-term mortality in stroke patients. (February 2014) - Hojs Fabjan, Tanja; Penko, Meta; Hojs, Radovan
Abstract Renal dysfunction is associated with mortality in patients after ischemic stroke. Cystatin C is a potentially superior marker of renal function compared to creatinine and estimated glomerular filtration rate (GFR). In our observational cohort study, 390 Caucasian patients suffered from acute ischemic stroke (mean age 70.9 years; 183 women and 207 men) were included and prospectively followed up to maximal 56 months. Serum creatinine and cystatin C were measured at admission to the hospital; GFR was estimated according to CKD-EPI creatinine and CKD-EPI creatinine/cystatin equations. According to values of serum creatinine, estimated GFR and serum cystatin C patients were divided into quintiles. In the follow-up period, 191 (49%) patients died. For serum cystatin C and estimated GFR based on creatinine and cystatin C, the mortality and the hazard ratios for long-term mortality increased from the first to the fifth quintile nearly linearly. The associations of serum creatinine and estimated GFR categories based on creatinine with long-term mortality were J-shaped. As compared with lowest quintile of serum cystatin C, the fifth quintile was associated with long-term mortality significantly also after multivariate adjustment (age, gender, initial stroke severity, known risk factors for stroke mortality). In contrast, in adjusted analysis serum creatinine and estimated GFR (CKD-EPI creatinine and CKD-EPI creatinine/cystatin) were not associated with long-term mortality. In summary, serum cystatin C was independently and better associated with the risk of long-term mortality in patients suffering from ischemic stroke than were creatinine and estimated GFR using both CKD-EPI equations.